Extended family health and basic care center (NASF-AB): an evaluative study on its actions with hypertensive and diabetic people NASF-AB: a study evaluation - Gomes, Adenilson da Silva; Martelli, Petrônio José de Lima; Cesse, Eduarda Ângela Pessoa; Gomes, Mariana Farias; dos Santos, Rebecca Soares de Andrade Fonseca; Chagas, Maria Bernadete Ribeiro; Costa, Juliana Martins Barbosa da Silva (Journal of Health Care, 2021)
promoted by the Extended Family Health and Basic Care Center (NASF-AB) is a relevant element for evaluative studies. Objective: to evaluate the implementation of NASF-AB in relation to its actions of food/nutrition and physical activity/body practices in the care of hypertensive and diabetic patients in the family health strategy (ESF) of Petrolina - PE. Methodology: This is an evaluative study of type 1b implantation analysis, which identified the degree of implantation (GI) of the NASF-AB and the influence of political and structural contextual factors. Results: It was found that the GI and its structure and process dimensions were partially implemented. When analyzing the context, it was found that it was favorable to implementation so that the political approach was more favorable than the structural approach. In turn, the NASF-AB process was favorably influenced by political factors such as knowledge about the NASF-AB, institution of partnerships, increased responsibilities and innovation in practices, however, the structure was unfavorably influenced by factors such as the physical structure of health units, team climate, professional ties and investments in NASF-AB. Conclusion: The partial implantation reveals the need to overcome strong obstacles so that this policy is able to induce effective improvements in the care of hypertensive and diabetic patients in the ESF.
Keywords: health evaluation; diabetes mellitus; systemic arterial hypertension; health care